Postplacental Placement of Intrauterine Devices: Acceptability, Reasons for Refusal and Proposals to Increase its Use - Maria Beatriz de Paula Leite Kraft; Mariana Miadaira; Marcos Marangoni Júnior; Cássia Raquel Teatin Juliato; Fernanda Garanhani Surita (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate the acceptability of postplacental placement of intrauterine devices (PPIUD), reasons for refusal and suggested policies to increase its use. Methods Cross-sectional study conducted at the Women Hospital of the Universidade de Campinas, Campinas, SP, Brazil. Postplacental placement of intrauterine devices was offered to women admitted in labor who did not present infections, uterinemalformation, twin pregnancy, preterm birth, and were at least 18 years old. In case of refusal, the parturient was asked to give their reasons and the answers were classified as misinformation about contraception or other reasons. The following were considered misinformation: fear of pain, bleeding, contraception failure and future infertility. Bivariate analysis was performed. Results Amongst 241 invited women, the refusal rate was of 41.9%. Misinformation corresponded to 50.5% of all refusals, and the reasons were: fear of pain (39.9%); fear of contraception failure (4.9%); fear of bleeding (3.9%); fear of future infertility (1.9%); other reasons for refusal were 49.5%. Parturients aged between 18 and 27 years old refused the PPIUD more frequently due to misinformation (67.4%), and older parturients (between 28 and 43 years old) refused frequently due to other reasons (63.6%) (p=0.002). Themean age of those who declined the PPIUD due to misinformation was 27.3 ± 6.4 years old, while those who declined for other reasons had a mean age of 29.9 ± 5.9 years old (p=0.017). Conclusion The refusal of the PPIUD was high, especially amongst young women and due to misinformation. It is necessary to develop educative measures during antenatal care to counsel women about contraception, reproductive health and consequences of unintended pregnancy.